Relationship Between The Quantity And Intensity Of Potassium In Some Maize Soils Of Central Kashmir (India) (Applied Biological Research, 2014)
Plant K uptake depends on its intensity, capacity and removal rate of soils  which can be modeled using K exchange-equilibrium obtained from  quantity-intensity (Q/I) isotherms i.e. activity ratio at equilibrium (AReK),  labile K (KL), potential buffering capacity (PBCK) and free energy change  (-∆G). These relations were studied in five major maize growing soils of  district Ganderbal (Kashmir, India). AReKranged from 0.26 to 1.21 x 10-3  (Mol L-1)0.5, KL from 0.26 to 0.67 cmolc kg-1, PBCKfrom 23.2 to 37.6 cmolc kg-1/(Mol L-1)0.5 and -∆G from 3.98 to 4.81 K cal mol-1oK-1. AReK was found  significantly correlated with clay (r = 840**) and K0 (r = 988*). Magnitude  of labile K (KL), K held on non-specific sites (K0) and specific sites (KX)  were higher in Sumbal silty clay. The negative values of ∆G indicated that  K- (Ca + Mg) exchange in all the soils was spontaneous.